2016
DOI: 10.1002/cam4.585
|View full text |Cite
|
Sign up to set email alerts
|

CD68+ cell count, early evaluation with PET and plasma TARC levels predict response in Hodgkin lymphoma

Abstract: Early response evaluation with [18F]fluordeoxyglucose (FDG) positron emission tomography after 2 cycles of chemotherapy (interim PET) has been indicated as the strongest predictor for outcome in classical Hodgkin lymphoma (HL). We studied the prognostic role of the number of tumor‐infiltrating CD68+ cells and of the plasma levels of TARC (thymus and activation‐regulated chemokine) in the context of interim PET in 102 patients with classical HL treated with Adriamycin, Bleomycin, Vinblastine, Dacarbazine (ABVD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 37 publications
6
15
0
Order By: Relevance
“…Furthermore, better response to treatment was observed in patients with reduced CD68 expression (by Rt-PCR, FCM and/or IHC), age lower than 40 years old, patients presented with early disease stage, and in those who were positive for CD20 protein expression. Our data in this context are in agreement with some previous reports including the study of Cuccaro et al [30], who demonstrated that the evaluation of the number of CD68 positive cells and B-symptoms at diagnosis could help to categorize low-risk patients regardless of the positive interim PET. They reported also that CD68 positive cells and B-symptoms were strong predictors for DFS in the assessed HL patients from Italy.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, better response to treatment was observed in patients with reduced CD68 expression (by Rt-PCR, FCM and/or IHC), age lower than 40 years old, patients presented with early disease stage, and in those who were positive for CD20 protein expression. Our data in this context are in agreement with some previous reports including the study of Cuccaro et al [30], who demonstrated that the evaluation of the number of CD68 positive cells and B-symptoms at diagnosis could help to categorize low-risk patients regardless of the positive interim PET. They reported also that CD68 positive cells and B-symptoms were strong predictors for DFS in the assessed HL patients from Italy.…”
Section: Discussionsupporting
confidence: 93%
“…Regarding the expression of CD68, its expressions by FCM and/or IHC were independent prognostic factors for OS, while only its expression by FCM was independent prognostic factors for DFS. These data are in concordance with many recent studies [30,32] reported that the number of CD68+ macrophages (by IHC) outperformed the international prognostic score (IPS) in adult cHL by multivariate analysis. Similarly, Koh et al observed that CD68 (by IHC) was independent prognostic factor for DFS, and it was not an independent prognostic marker for OS in cHL patients [23].…”
Section: Discussionsupporting
confidence: 92%
“…TARC is highly expressed in HRS cells that form a small minority of the cHL tumor mass (11, 12). TARC levels are highly increased in cHL patient sera and plasma, and these levels decrease in most clinical responders (13, 14).…”
Section: Resultsmentioning
confidence: 99%
“…The reported positive predictive values of PET/CT in cHL patients are generally lower relative to the negative predictive values (10). TARC (thymus and activation-regulated chemokine, also known as cysteine-cysteine ligand 17 [CCL17]) is a chemokine produced by HRS cells that may have a role in shaping a favorable immune microenvironment (11, 12). TARC levels are increased in the sera of cHL patients and may also reflect tumor status, since elevated levels decrease during treatment in most clinical responders (13, 14).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies are exploring the combination of interim-PET results with additional parameters derived from baseline imaging [25], or from lymphoma tissue analysis and biological biomarkers [26][27][28][29]. One team showed that textural analysis of baseline CT images are correlated to progression-free survival and can be combined with information from interim-PET [30].…”
mentioning
confidence: 99%